PENGARUH LATIHAN SIDE JUMP/SPRINT TERHADAP DAYA LEDAK OTOT TUNGKAI PADA TIM PENCAK SILAT PUTRI SMP N 6 RUMBAI PEKANBARU - Deswanti, Mezra; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is that there are still athletes who do not have the elements of good physical condition such as the maximal limb muscle explosive power, which can be seen from the kick ability is not good, it is caused by the lack of explosive muscle power of the limbs so that the kick becomes not maximal, and lacking in power, lack of maximal kick speed and not sliding hard. Therefore the female martial arts team must be given side jump / sprint training which is one form of exercise that trains the explosive power of the leg muscles so that it will be very useful for the fighter in doing kick techniques. The purpose of this research was to determine the effect of side jump / sprint training on the explosive strength of leg muscles in the female martial arts team of SMP N 6 Rumbai Pekanbaru. The hypothesis proposed is that there is the effect of side jump / sprint exercises on the explosive power of leg muscles on the female martial arts team of SMP N 6 Rumbai Pekanbaru. The population in this research is the 12 female martial arts team of SMP N 6 Rumbai Pekanbaru, totaling 12 people. The sampling technique used was total sampling so that the number of samples in this research were 12 people. The instrument used to collect data is the pree test and standing broad jump test. The data analysis technique used is the t test. Based on the results of the analysis of pree test and post test data there was an increase of an average of 3.23% with a t test that tcount = 14.119> from t table = 1.796. Then it can be concluded that there is a significant effect of side jump / sprint training on leg muscle explosive power in the female martial arts team of SMP N 6 Rumbai Pekanbaru.Keywords: Side Jump / Sprint, Limb Muscle Power.